2020
DOI: 10.1038/s41598-020-71986-9
|View full text |Cite
|
Sign up to set email alerts
|

Foveated near-eye display using computational holography

Abstract: Holographic display is the only technology that can offer true 3D with all the required depth cues. Holographic head-worn displays (HWD) can provide continuous depth planes with the correct stereoscopic disparity for a comfortable 3D experience. Existing HWD approaches have small field-of-view (FOV) and small exit pupil size, which are limited by the spatial light modulator (SLM). Conventional holographic HWDs are limited to about 20° × 11° FOV using a 4 K SLM panel and have fixed FOV. We present a new optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…According to the tracked positions of the pupil, the tilt terms (such as the lens or grating terms) could be directly added to the computer‐generated hologram. [ 129 ] As the pupils rotated and then tracked by the pupil‐tracker camera to calculate the gaze angle, the hologram would be updated to retain the image's high resolution on the pupils' rotation center. However, due to the smaller size of the near‐eye display panel, the eyebox's movement may be limited.…”
Section: Ar/vr Holographic Near‐eye Display Systemmentioning
confidence: 99%
“…According to the tracked positions of the pupil, the tilt terms (such as the lens or grating terms) could be directly added to the computer‐generated hologram. [ 129 ] As the pupils rotated and then tracked by the pupil‐tracker camera to calculate the gaze angle, the hologram would be updated to retain the image's high resolution on the pupils' rotation center. However, due to the smaller size of the near‐eye display panel, the eyebox's movement may be limited.…”
Section: Ar/vr Holographic Near‐eye Display Systemmentioning
confidence: 99%
“…Computational holography is a technology that utilizes computer algorithms to intelligently process optical holographic images, enabling precise generation and efficient reconstruction. [1][2][3] This technology has gained significant attention in the current trend of deep learning, as it offers new possibilities for the development and application of optical techniques. 4 Computational holography finds wide applications in various fields such as medical imaging, 5,6 3D display, 7,8 and security inspection.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the current holographic display systems fail to fulfill the spatiotemporal requirements of AR/VR devices due to the limited size of the synthesized images and the extent of the corresponding viewing angles. Earlier research on the subject showed that a wavefront modulator in a wearable AR/VR device must have ~50K × 50K pixels ( 11 ), ideally with a pixel pitch smaller than the wavelength of the visible light. Such an SLM is beyond the reach of current technology, considering that the state-of-the-art SLMs can offer resolutions up to 4K (e.g., 3840 horizontal and 2160 vertical pixels), with a pixel pitch that is typically 5- to 20-fold larger than the wavelength of the light in the visible part of the spectrum.…”
Section: Introductionmentioning
confidence: 99%